Note: Rating Accessibility of Packaging: A Medical Packaging Example. Issue 12 (December 2016) - Rowson, Jen; Sangrar, Aamir; Rodriguez‐Falcon, Elena; Bell, Alison F.; Walton, Karen A.; Yoxall, Alaster; Kamat, Seri Rahayu
Abstract : The article from this special issue was previously published in Packaging Technology in Science, Volume 27, Issue 7, 2014. For completeness we are including the title page of the article below. The full text of the article can be read in Issue 27:7 on Wiley Online Library:http://onlinelibrary.wiley.com/doi/10.1002/pts.2049/abstract